2017
DOI: 10.1089/tmj.2016.0144
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Information System Analysis of Healthcare Need and Telemedicine Delivery in California

Abstract: Originating sites receiving telemedicine services from a university-based telemedicine program were located in regions with significantly higher community healthcare needs. Leveraging a geospatial information system to understand community healthcare needs provides an opportunity for payers, hospitals, and patients to be strategic in the allocation of telemedicine services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Every day, new generations of technologies and mobile communications with many different capabilities are developed. To introduce and familiarize relief workers with these new technologies, it seems necessary to hold training courses [13]. The communication equipment was at an excellent level, which confirms the results of the Taylor et al study.…”
Section: Communication Equipment Requirements and Equipment And Medicsupporting
confidence: 76%
“…Every day, new generations of technologies and mobile communications with many different capabilities are developed. To introduce and familiarize relief workers with these new technologies, it seems necessary to hold training courses [13]. The communication equipment was at an excellent level, which confirms the results of the Taylor et al study.…”
Section: Communication Equipment Requirements and Equipment And Medicsupporting
confidence: 76%
“…9,10 Prior studies have explored geographic data for modeling appropriate locations in which to establish rural telehealth centers, or to determine if existing telehealth services target communities of greatest need. 11,12 However, outside of survey-based methods, no specific analyses have been done in the United States to examine the feasibility or outcomes of providing TAH in rural areas. Telehealth is most needed in rural areas, owing to factors, such as distance, that limit access to in-person care compared to urban populations.…”
Section: Introductionmentioning
confidence: 99%
“…Regionally, we previously found that nearly half of New England EDs use telemedicine, most frequently for stroke and neurology care. 22 And while other studies have described telemedicine utilization regionally 23 or for specific clinical applications, 8,10,24 none have provided data on the prevalence of telemedicine use in EDs nationally.…”
Section: Introductionmentioning
confidence: 99%